Anatomical Studies on the Reticulum of Adult Non-Descript Sheep of Jammu Region - Sasan, Jasvinder Singh; Suri, Shalini; Sarma , Kamal (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Present study was carried out on six stomach samples from adult apparently healthy non-descript sheep. Reticulum was spherical and  was separated from rumen by rumino-reticular groove ventrally. Mucosa was pale brown in colour. Reticular cells were subdivided by  secondary and tertiary crests. Mean empty weight of reticulum was 13.11% of the total empty weight of the stomach whereas the  capacity was 6.04% of the total volume of the stomach. The dorso-ventral height of reticulum was greater than its cranio-caudal width.  Histologically, reticulum consisted of tunica mucosa, tunica submucosa, tunica muscularis and tunica serosa. Lamina epithelialis was  lined by keratinized stratified squamous epithelium. Lamina muscularis mucosae was present only towards the tip of primary reticular  crests. Tunica muscularis had inner circular and outer longitudinal layers of smooth muscle.Thickness of outer muscular layer, length of  reticular crest and width of reticular crest showed significant difference (p
Keywords: Anatomy; Histology; Histochemistry; Reticulum; Sheep